The Impact of Body Mass Index on Freedom From Therapeutic Intervention and Quality of Life in Active Surveillance Prostate Cancer Patients. (August 2021) - Merrick, Gregory S.; Galbreath, Robert; Fiano, Ryan; Scholl, Whitney; Bennett, Abbey; Butler, Wayne M.; Kurko, Brian; Adamovich, Edward
Abstract : Objective: The objective of this study was to evaluate the impact of body mass index (BMI) on overall survival, freedom from distant metastases, rates of therapeutic intervention (TI), and quality of life (QOL) in active surveillance (AS) prostate cancer patients. Materials and Methods: Three hundred forty consecutive, prospectively evaluated AS patients underwent a staging transperineal template-guided mapping biopsy before AS enrollment and were stratified by BMI (<25, 25 to 29.9, 30 to 34.9, and >35 kg/m 2 ). Evaluated outcomes included overall survival, freedom from distant metastases, TI, QOL to include urinary, bowel, sexual function and depression and serial postvoid residual urine measurements. The relationship between BMI and anterior prostate cancer distribution was evaluated. Repeat biopsy was based on prostate specific antigen kinetics, abnormal digital rectal examination and patient preference. Results: Of the 340 patients, 323 (95%) were Gleason 3+3 and 17 patients (5.0%) were Gleason 3+4. The median follow-up was 5.2 years (range: 1 to 14 y). At 10 years, TI was instituted in 4.7%, 2.2%, 9.5%, and 25.0% of patients in BMI cohorts <25, 25 to 29.9, 30 to 34.9, and ≥35 ( P =0.075). No patient has developed distant metastases. The median time to TI was 4.86 years. In multivariate analysis, TI was most closely predicted by prostate specific antigen density ( P =0.071). At 8 years, no statistical differences in urinary function, bowel function, depression or postvoid residual were noted. However, a trend for erectile dysfunction was identified ( P =0.106). Conclusion: At 10 years, BMI did not statistically predict for TI, geographic distribution of prostate cancer or QOL parameters.